Modos de aplicação de zinco na nutrição e no crescimento inicial da cultura do arroz - Ribeiro Correia, Marcus Andre [UNESP]; Prado, Renato de Mello [UNESP]; Collier, Leonardo Santos; Rosane, Danilo Eduardo; Romualdo, Liliane Maria (Universidade Federal de Uberlândia (UFU), 2008)
The present research had he objective to evaluate rice response to zinc application forms on the nutrition, growth and dry matter production, in vase conditions. The experiment was carried out in a completely randomized design, with five treatments (leaf Zn, incorporated Zn, located Zn, Zn saw seed and witness - whitout zinc), in four repetitions during two cycles of cultivation with 42 days of duration each. Plastic vase of 7L, were filled with Red Distrofic Latosol (Zn = 0.3 mg dm(-3) in DTPA). The application of Zn saw soil in both culture of the rice improved its level in the soil, being distinguished it from located form. In the first cycle, the application of Zn saw leaf promoted greater absorption of the nutrient for the rice plants, while in the second cycle leaf application was followed by the saw soil incorporated. The biggest dry matter production occurred with application of leaf saw in the first cycle and saw soil (incorporated and located) in the second rice cultivation.

O modo de aplicação do zinco na cultura do arroz, poderá afetar a absorção do micronutriente e o crescimento da planta. Deste modo, o presente trabalho objetivou avaliar a resposta do arroz a modos de aplicação de Zn sobre a nutrição, crescimento e produção de matéria seca cultivado, em condições de vaso. O delineamento experimental utilizado foi inteiramente casualizado, com cinco tratamentos (Zn foliar, Zn incorporado, Zn localizado, Zn via semente e testemunha), em quatro repetições durante dois cultivos com 42 dias de duração cada. Utilizou-se vaso plástico de 7 L, preenchido com Latossolo Vermelho Distrófico (Zn = 0,3 mg dm-3 em DTPA). A aplicação de Zn via solo em ambos cultivo do arroz incrementou o seu teor no solo, destacando-se a forma localizada. No primeiro cultivo, a aplicação de Zn via foliar promoveu maior absorção do nutriente pelas plantas de arroz, enquanto no segundo cultivo destacou-se a aplicação foliar e em seguida a aplicação via solo incorporado. A maior produção de matéria seca ocorreu com aplicação de Zn via foliar no primeiro cultivo e via solo (incorporado e localizado) no segundo cultivo.
Zinc forms of application in the nutrition and the initial growth of the culture of the rice
Keywords: Micronutrient; Oryza sativa L.; Sources and levels of fertilization